A split screen system to analyse coach behaviour: a case report of coaching practice - Brown, E.; O'Donoghue, P. (International Journal of Computer Science in Sport, 2008)
The analysis of coach behaviour using information and communications technology has become an established area of research. Advances in the application of information technology have lead to analysis systems for sports being integrated with match video allowing interactive video feedback to be provided in an efficient and flexible manner. Commercial video analysis packages are not only useful for analysing player behaviour in sport, but can also be used to analyse coach behaviour. The purpose of the current exercise was to implement a coach behaviour analysis system using the Dartfish TM package to allow a netball coach's behaviour to be analysed so that the quantitative breakdown of the coach's behaviour could be supported by video sequences of examples of behaviours of interest within a process of reflective practice. A split screen video displaying a close up view of the coach as well as a wider view of the coaching session was analysed. The coach found the video sequence feedback to be more useful than the quantitative information produced. The specific phases of reflective practice where the system could provide the most benefit are issue identification, experimentation and evaluation.